A comparison of NMR scan to transrectal ultrasound – measured prostate volume in untreated prostate cancer - Terlikiewicz, Joanna; Makarewicz, Roman; Lebioda, Andrzej; Wronczewska, Anna; Kabacińska, Renata; Zuchora, Anysja (Contemporary Oncology/Współczesna Onkologia, 2006)
Purpose: Prostate cancer is one of the most common malignancies in men in developed European countries. Disease confined to the prostate gland can be definitively treated with radical radiation therapy. There are some diagnostic procedures like NMR, CT, TRUS and transabdominal ultrasound which can be used in the diagnostic and treatment planning of prostate cancer. A lot of controversial opinions exist about which method is the best in diagnosis of prostate cancer. The aim of our work was to compare NMR and TRUS–measured prostate volume in untreated prostate cancer. Material and methods: Prostate volume was assessed using NMR and TRUS in 30 patients with prostate cancer. Patients were treated in the Oncology Centre in Bydgoszcz in 2005-2006 using brachytherapy and teleradiotherapy. Pearson’s correlation coefficient and linear regression parameters were calculated using Statistica for Windows v 7. Results: Prostate volume estimated using NMR was larger than the TRUS volumes. The mean NMR volume was 44.5 cm 3 and the mean TRUS volume was 32.9 cm 3 . Pearson correlation coefficient was 0.73 (0.61-0.85 CI 95%, p<0.0001). Conclusions: A significant correlation was found between NMR and TRUS measurements of prostate volume. In our opinion it is possible that NMR overestimated the prostate volume by approximately 25%. It seems that TRUS is an important diagnostic method in the assessment of prostate volume.